Serbian: Serbian - Obradovic, Danilo; Serbian, Serbian (Medicinski podmladak, 2022)
Endometrial carcinomas (EC) represent the most common malignant tumors of the female reproductive system and the sixth most common in the female population with an increased incidence of morbidity and mortality over the past three decades. In addition to stage, grade and type of tumor are the most significant prognostic factors of the biological behavior of EC and in current clinical practice are based on pathohistological examination. The shortcomings of the current histological classification are cited as one of the key limiting factors in further research, as well as in the understanding of EC carcinogenesis and improving therapeutic protocols. A new molecular classification of EC was formulated, based on the analysis of molecular biological features, recognized as highly related to the specific clinical course. Considerable efforts have been made to understand the process of angiogenesis as one of the key processes in tumor growth. The vascular endothelial growth factor (VEGF) family is a group of proangiogenic ligands that play a central role in the process of physiological and pathological angiogenesis. VEGF is the most widely investigated angiogenic factor as a potential biomarker and target for targeted therapy. After vast research, clinical studies have shown significant advances in the development of anti-angiogenic therapy directed at VEGF, predominantly in the form of combined therapy. In defining therapeutic groups, this therapy relies on the molecular classification of EC. Antiangiogenic therapy is limited to small specific groups of patients, is associated with side effects, and many patients who initially responded to targeted therapy develop resistance over time, which indicates the further need for a better understanding of the mechanisms and factors involved in the angiogenic process of EC. Potentially promising advances in the development of targeted therapeutic options for EC can be expected within the integration of molecular features of EC as a factor in the context of histological classification.
Keywords: Serbian